USING ANIMATED VIDEO IN TEACHING WRITING - Roswita M. Aboe (FKIP Universitas Khairun, 2021)
The objective of this study was to explore the effectiveness of using animated video in teaching descriptive writing at the fifth semester students of English Education study program of Khairun University. This research employed quantitative descriptive method from which the data of the test are taken from pre and posttest. 20 respondents were chosen by purposive sampling technique to be involved in this research. The data collection technique in this study was a test prior to teach writing using animated video and a posttest after that. From the data analysis of pretest, the respondent obtained the average score of 59.58 whereas their posttest score was 76.18. The score raised 16.60 points from the first to the second test. Overall, using animated video was proved effective in teaching descriptive writing at the fifth semester students of English education study program.